Patients’ Experiences of Ending Massage Therapy Care: a Commentary - Baskwill, Amanda (Int J Ther Massage Bodywork, 2020)
Patients are best positioned to provide information about their experiences of healthcare services; however, their perspectives are often underutilized. During informal discussions with massage therapists (MTs) and through the authors’ own professional experiences, it was noted that there are times when patients decide independently, and without notice, to end the care they are receiving. To date, no research has been published exploring the experiences of patients who choose to discontinue massage therapy care and there is a gap in the quality assurance process of MTs. Lack of understanding of patients’ experiences is a missed opportunity to strengthen the therapeutic relationship, ensure patient safety, improve treatment quality, and develop professionally. We recommend researchers explore mixed methods designs, involve patients in the research process, and solicit multiple perspectives when studying patients’ experiences of ending massage therapy care.